Morphological changes in the rat’s liver of different age after administration of magnesium chloride - Yanko, Roman V.; Chaka, Elena G.; Litovka, Irina G.; Levashov, Mikhail I. (Experimental Biology and Biotechnology, 2019)
The aim of the work was to study the morphological changes in the rat’s liver of different ages after prolonged administration of magnesium chloride. The experiments were performed on 48 Wistar male rats at 3 and 15 months of age. Experi mental animals, in addition to the standard diet, received magnesium chloride daily for 21 days at a dose of 50 mg / kg of body weight. Histological preparations were made from the liver tissue according to the standard method. The liver morphometry was performed on digital images using the computer program Image J. The content of magnesium cations was determined in the serum and suspension of red blood cells. Based on the results of our studies, it can be assumed that the administration of magnesium chloride activates the processes of physiological regeneration and functional activity of the liver parenchyma in rats of different ages. This is evidenced by an increase in the number of binuclear cells and nucleolus in the nucleus of hepatocytes, an increase in the nuclear-cytoplasmic and nucleolar-nuclear ratio. The relative area of the sinusoid network, the number and density of connective tissue cells were increased in the liver of 3-month-old experimental rats. This may indicate an increase of trophic and protective activity of the stroma in this organ. Experimental rats (15-month-old animals) revealed a moderate increasing in the erythrocyte suspension and blood serum magnesium content. The administration of magnesium chloride has the morphological features indicating an increasing of the physiological regeneration and activity of the liver parenchyma in young (to a greater extent) and adult animals.